Coffee and acute ischemic stroke onset: the Stroke Onset Study - Mostofsky, E; Schlaug, G; Mukamal, K J; Rosamond, W D; Mittleman, M A (Neurology, 2010)
Prior research suggests an acutely elevated risk of myocardial infarction and sudden cardiac death in the hour after coffee intake. However, the risk of ischemic stroke associated with transient exposure to coffee remains unclear. We hypothesized that caffeine intake is associated with a transiently increased risk of ischemic stroke. In this multicenter case-crossover study, we interviewed 390 subjects (209 men, 181 women) between January 2001 and November 2006 a median of 3 days after acute ischemic stroke. Each subject's coffee consumption in the hour before stroke symptoms was compared with his or her usual frequency of consumption in the prior year. Of the 390 subjects, 304 (78%) drank coffee in the prior year, 232 within 24 hours and 35 within 1 hour of stroke onset. The relative risk (RR) of stroke in the hour after consuming coffee was 2.0 (95% confidence interval [CI], 1.4-2.8; p < 0.001). There was no apparent increase in risk in the hour following consumption of caffeinated tea (RR = 0.9, 95% CI 0.4-2.0; p = 0.85) or cola (RR = 1.0, 95% CI 0.4-2.4; p = 0.95). The association between ischemic stroke in the hour after coffee consumption was only apparent among those consuming ≤1 cup per day but not for patients who consumed coffee more regularly (p for trend = 0.002). Relative risks remained similar when the sample was restricted to those who were not simultaneously exposed to other potential triggers and the results remained significant after stratifying by time of day. Coffee consumption transiently increases the risk of ischemic stroke onset, particularly among infrequent drinkers.